Optimization study of finite element simulation based on multi-layer structure and anisotropic CFRP - Yu-xin, Qin; Xin-meng, Xiong; Wen-li, Zhang (Frontiers in Materials, 2023)
Current research has mostly simplified CFRP components as isotropic media or homogenized them as anisotropic media, which fails to present the actual acoustic propagation behavior inside the CFRP components and restricts the accuracy of decoupling sound line tracking results and defect feature information. Based on clarifying the influence of fiber direction on the spatial distribution of CFRP elastic properties, this paper proposes an acoustic modeling method for CFRP multi-directional plates considering the coupling effect of multi-layer structure and elastic anisotropy. There are two main innovations: 1. The model is optimized using the Voigt representation method, which can quantitatively characterize the elastic anisotropy of any homogeneous material with a 6x6 elastic stiffness matrix containing 21 independent elastic constants. In this paper, the elastic stiffness matrix only includes five independent elastic constants; 2. Finite element simulation is used to analyze the propagation rules of ultrasonic waves inside CFRP and compare the detection methods with or without sound coupling layer. The acoustic characteristics of the sound coupling layer are changed to find the optimal coupling method, reduce the refraction of ultrasonic waves in the specimen layer, and make the sound line path more accurate.